Indigenous Autonomy, Community-Based Research, and Development aid: Sumaq kawsay in three epistemic scenarios. (September 2016) - Gonzales, Tirso; Husain, Matt
In this paper, the future of Indigenous autonomy and Indigenous community-based research is illustrated by analyzing re-Westernization, de-Westernization, and decoloniality in relation to the regeneration of the Indigenous glocal (global/local) concept of sumaq kawsay ("living well" in Quechua). The regeneration of sumaq kawsay as a new geopolitical and cultural polycentric and multipolar world is examined from an Indigenous studies decolonial perspective and an Indigenous Andean campesino (peasant) community-based perspective. Sumaq kawsay has encouraged an unexpected pan-Latin American perspective that supports decoloniality and its epistemic pluri-versity as an alternative scenario to "progress" and the business approach of development aid embedded within re-/de-Westernization.